Prevalence of Sarcopenia Among the Elderly in Korea: A Meta-Analysis - Yoo Jin Choo; Min Cheol Chang (Korean Society for Preventive Medicine, 2021)
Objectives Sarcopenia is a common disease in the elderly population that causes disability, poor quality of life, and a high risk of death. In the current study, we conducted a meta-analysis to report basic knowledge about the prevalence of sarcopenia in the elderly in Korea. Methods We searched for articles in the MEDLINE, Cochrane Library, Embase, and Scopus databases published until December 28, 2020. Studies investigating the prevalence of sarcopenia in elderly Koreans aged ≥65 years were included. The methodological quality of the studies was evaluated using the Newcastle-Ottawa scale. Publication bias was evaluated using the Egger test and funnel plots. Results In total, 3 studies and 2922 patients were included in the meta-analysis. All 3 studies used the European Working Group on Sarcopenia in Older People criteria for the diagnosis of sarcopenia. The total prevalence of sarcopenia was 13.1-14.9% in elderly men and 11.4% in elderly women. Conclusions This meta-analysis is the first to estimate the pooled prevalence of sarcopenia in elderly Koreans, and its findings suggest that sarcopenia is common in this population. Therefore, attention should be paid to the prevention and control of sarcopenia.